2015
DOI: 10.3109/15376516.2015.1028605
|View full text |Cite
|
Sign up to set email alerts
|

PCB 77 action in ovary cells – toxic effects, apoptosis induction and cell cycle analysis

Abstract: These results indicate toxic outcomes of PCB 77 at ovarian cellular level with regard to potential direct adverse effects to female reproductive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
4
5
1
Order By: Relevance
“…Time dependency was also evident in the increase in the apoptotic peak at 48 h (Figure 4A). We reported similar findings for PCB 77 earlier (13) and Venkatesha et al ( 5) also reported that PCB 153 inhibited the entry of MCF-10A human mammary epithelial cells into the S-phase, while the proportion of G1 cells remained high (90-95 %).…”
Section: Effects Of Pcb 153 On Cell Cycle Progression In Cho-k1 Cellssupporting
confidence: 87%
See 3 more Smart Citations
“…Time dependency was also evident in the increase in the apoptotic peak at 48 h (Figure 4A). We reported similar findings for PCB 77 earlier (13) and Venkatesha et al ( 5) also reported that PCB 153 inhibited the entry of MCF-10A human mammary epithelial cells into the S-phase, while the proportion of G1 cells remained high (90-95 %).…”
Section: Effects Of Pcb 153 On Cell Cycle Progression In Cho-k1 Cellssupporting
confidence: 87%
“…Variations in IC 50 values between the four assays suggest that combining multiple assays with different endpoints (such as membrane integrity, lysosomal activity, total cellular protein content, and mitochondrial function) can provide valuable information about possible mechanisms of action of the tested compound. Compared to the IC 50 values obtained for planar dioxin-like PCB 77 from our previous study (13), non-planar di-orthosubstituted PCB 153 in this study (Table 1) showed a much weaker toxic effect on ovarian cells, especially after prolonged exposure.…”
Section: Reactive Oxygen Species Determinationcontrasting
confidence: 82%
See 2 more Smart Citations
“…Results have shown that PCB 153 triggers a homeoviscous response by changing cholesterol content in liver (+51%) and brain (+216%), as well as the double bond index in gills (−17%). Previous study conducted in our laboratory (Murati et al, 2015) suggests specific damage in the cellular membranes, and alterations affecting the proliferation, metabolism and/or adhesion of ovarian cells after PCB 77 treatments. Our group also investigated correlation of PCB cytotoxicity with chlorine substitution and pointed out statistically significant cytotoxicity after exposure to both (DL and ortho ‐substituted) PCBs with slightly profound effects of DL PCB 77.…”
Section: Polychlorinated Biphenyl Congener Specific Effects On Cell Mmentioning
confidence: 77%